STUDI SIFAT FISIS DAN MEKANIS KOMPOSIT TAMBAL GIGI KOMERSIAL - , AL ICHLAS IMRAN; , Dr. Kusmono, S.T., M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Restorative dental composites are classified in three types, namely microfilled, nanofilled and nanohybrid composites. The mechanical properties of restorative dental composites are influenced by the matrix, filler, polymerization and a wet oral environment. The aims of this study were to determine and compare the physical and mechanical properties of three types of commercial restorative dental composites, study the behavior of the water absorption and its effect on mechanical properties. The commercial restorative dental composites used were Solare®X-A3 (microfilled), FiltekTMZ350XT Flow-A3 (nanofilled) and Grandio®Flow-A3 (nanohybrid). The immersion media used were artificial saliva (pH-7) and Coca- Cola® (pH-3.45). Each specimen was made by acrylic mold and hardened by light curing for one minute. Before immersion, the mechanical properties were determined through bending, compressive and fracture toughness tests. The behavior of water absorption was done by immersion the specimen was in artificial saliva or Coca-Cola® Before immersion, Filtek showed the highest bending strength (95.45 MPa), followed by Grandio (59.08 MPa) and Solare (22.62 MPa). Grandio showed the highest values in compressive strength and fracture toughness (146.46 MPa and 13.28 MPa.mm media. The weight increase of specimen was recorded periodically every 1 to 4 days for 38 days. After immersion, the mechanical properties were determined through bending and compressive tests. The bending fractured surface and chemical analysis Filtek composite was observed by scanning electron microscope (SEM) and energy dispersive spectrometry (EDS), respectively. 1/2), followed by Filtek (120.67 MPa and 7.16 MPa.mm1/2) and Solare (85.37 MPa and 4.26 MPa.mm1/2), respectively. After immersion, Grandio showed the highest water sorption, followed by Filtek and Solare. Water absorption decreased the compressive and bending strength of three types of commercial dental composites. Immersion in Coca-Cola® resulted in the higher reduction in compressive and bending strength compared to immersion in artificial saliva. Key words: Restorative dental composites, water absorption, physical and mechanical properties